Molecular and biological characterization of two potyviruses infecting lettuce in southeastern France. (5th January 2017) - Desbiez, C.; Schoeny, A.; Maisonneuve, B.; Berthier, K.; Bornard, I.; Chandeysson, C.; Fabre, F.; Girardot, G.; Gognalons, P.; Lecoq, H.; Lot, H.; Millot, P.; et al.
Abstract : Several potyviruses affect lettuce ( Lactuca sativa ) and chicory ( Cichorium spp.) crops worldwide and are important constraints for production because of the direct losses that they induce and/or because of their seed transmission. Here, the molecular and biological properties are described of two potyviruses that were recently isolated from lettuce plants showing mosaic or strong necrotic symptoms in an experimental field in southeastern France. The first potyvirus belongs to the species Endive necrotic mosaic virus and is present in a large number of wild plant species, especially Tragopogon pratensis . It is unable to infect lettuce cultivars with a resistance to Turnip mosaic virus that is present in many European cultivars and probably conferred by the Tu gene. The second potyvirus belongs to the tentative species lettuce Italian necrotic virus and was not observed in wild plants. It infected all tested lettuce cultivars. Wild accessions of Lactuca serriola, Lactuca saligna, Lactuca virosa and Lactuca perennis were identified as resistant to one or the other potyvirus and could be used for resistance breeding in lettuce. No resistance against these two potyviruses was observed in the tested Cichorium endivia cultivars. In contrast, all tested Cichorium intybus cultivars or accessions were resistant.